Clinical application of a sub-fractionation workflow for intrafraction re-planning during prostate radiotherapy treatment on a 1.5 Tesla MR-Linac: A practical method to mitigate intrafraction motion. (November 2022) - Willigenburg, Thomas; Zachiu, Cornel; Bol, Gijsbert H.; de Groot-van Beugel, Eline N.; Lagendijk, Jan J.W.; van der Voort van Zyp, Jochem R.N.; Raaymakers, Bas W.; de Boer, Johannes C.J.
Highlights: A new intrafraction adaptive workflow for SBRT on a 1.5 T MR-Linac is presented. The sub-fraction workflow allows delivery of the fractional dose in multiple parts. Clinical feasibility of the workflow was shown for prostate cancer SBRT. The workflow reduced the systematic intrafraction prostate (target) motion. Using sub-fractionation, PTV margins of 2 and 3 mm can be safely adopted. Abstract: Background: Intrafraction motion during radiotherapy limits margin reduction and dose escalation. Magnetic resonance (MR)-guided linear accelerators (MR-Linac) have emphasised this issue by enabling intrafraction imaging. We present and clinically apply a new workflow to counteract systematic intrafraction motion during MR-guided stereotactic body radiotherapy (SBRT). Materials and methods: With the sub-fractionation workflow, the daily dose is delivered in multiple sequential parts (sub-fractions), each adapted to the latest anatomy. As each sub-fractionation treatment plan complies with the dose constraints, no online dose accumulation is required. Imaging and treatment planning are executed in parallel with dose delivery to minimise dead time, enabling an efficient workflow. The workflow was implemented on a 1.5 T MR-Linac and applied in 15 prostate cancer (PCa) patients treated with 5 × 7.25 Gy in two sub-fractions of 3.625 Gy (10 × 3.625 Gy in total). Intrafraction clinical target volume (CTV) motion was determined and compared to a workflow with single-plan delivery. Furthermore, required planning target volume (PTV) margins were determined. Results: Average on-table time was 42.7 min. Except for two fractions, all fractions were delivered within 60 min. Average intrafraction 3D CTV displacement (±standard deviation) was 1.1 mm (± 0.7) with the sub-fractionation workflow, whereas this was up to 3.5 mm (± 2.4) without sub-fractionation. Calculated PTV margins required with sub-fractionation were 1.0 mm (left–right), 2.4 mm (cranial-caudal), and 2.6 mm (anterior-posterior). Conclusion: Feasibility of the sub-fractionation workflow was demonstrated in 15 PCa patients treated with two sub-fractions on a 1.5 T MR-Linac. The workflow allows for significant PTV margin reduction in these patients by reducing systematic intrafraction motion during SBRT.